A CHEMOTAXONOMIC STUDY OF SOME SPECIES OF ZINGIBER SUBSECTION ZERUMBET - RUSDY E. NASUTION (Research Center for Biology, 1980)
Zingiber zerumbet (L.) J.E. Smith, Z. amaricans BL, Z. aromaticum Val., and Z. littorale Val., which Backer & Bakhuizen v.d. Brink treated as a single species named Z. zerumbet, have been found to be chemically and palynologically distinct. This vindicates the species formulation made by Valeton, in which they were distinguished as four separate species.